Accounting for the racial property crime gap in the US: A quantitative equilibrium analysis - Marco Cozzi (Queen's University, Department of Economics, 2010)
This paper studies the effects of both labor market conditions and asset poverty on the property crimes involvement of American males. Since the mid 60's the property crimes arrest rate has been four times higher for black males if compared to white ones. Another set of stylised facts show for the first demographic group lower educational levels and worse labor market outcomes, with the African Americans supplying less hours of labor, gaining lower wages, experiencing both higher unemployment duration and rates. At the same time, more than 30% of black households had a negative net worth. A dynamic general equilibrium model is developed, exploiting these facts to quantitatively assess the race crime gap, that is the difference in crime explained by the difference in observables. The model is calibrated relying on US data and solved numerically. The model captures well relevant dimensions of the crime phenomenon, such as the inmates composition by race, employment status and education. Simulation results show that the observed poverty and labor market outcomes account for as much as 90% of the arrest rates ratio. Finally the model is used to compare two alternative policy experiments aimed at reducing the aggregate crime rate: increasing the expenditure on police seems to be cost effective, when compared to an equally expensive lump-sum subsidy targeted to the high school dropouts.
Keywords: D52; D58; D99; J15; K42; 330; Property crimes; Computable General Equilibrium; Incomplete Markets; Race; Wealth Inequality; Kriminalität; Strafe; Strafvollzug; Ethnische Gruppe; Arbeitslosigkeit; Soziale Ungleichheit; Einkommen; USA